'True Democracy' as a Prelude to Communism The Marx of Democracy - Chrysis, Alexandros (Political Philosophy and Public Purpose,, 2018)
This book constitutes a critical intervention in the theoretical discussion over the political relationship between democracy and communism. Shedding light on the philosophical origins of the Democracy-debate, it draws a clear demarcation line between liberalism and republicanism, arguing that after rejecting the former and supporting the latter, the young Marx endorsed "true democracy" as a prelude to his forthcoming theory of communism. To this end, while following the dynamics of the Marxian history of political ideas and pre-communist theory of the state, the book takes into account the thought of a vast range of philosophers and political theorists, starting from the Ancient times (Aristotle), passing through the Age of Enlightenment (Spinoza, Rousseau), the German Idealist tradition (Hegel) the Young Hegelians' Republicanism (Bauer, Ruge, Feuerbach), and reaching our own times (Arendt, Colletti, MacPherson, Castoriadis, Poulantzas). It will be of interest to students and scholars interested in the history of political thought, theories of democracy, and Marxism. .